Cytoprotective agent troxipide-cyanine dye conjugate with cytotoxic and antiproliferative activity in patient-derived glioblastoma cell lines. (15th October 2021) - Cooper, Elizabeth; Choi, Peter J.; Schweder, Patrick; Mee, Edward; Turner, Clinton; Faull, Richard; Denny, William A.; Dragunow, Mike; I-H. Park, Thomas; Jose, Jiney
Graphical abstract: Abstract: Cytoprotective agents are mainly used to protect the gastrointestinal tract linings and in the treatment of gastric ulcers. These agents are devoid of appreciable cytotoxic or cytostatic effects, and medicinal chemistry efforts to modify them into anticancer agents are rare. A drug repurposing campaign initiated in our laboratory with the primary focus of discovering brain cancer drugs resulted in drug-dye conjugate 1, a combination of the cytoprotective agent troxipide and heptamethine cyanine dye MHI 148. The drug-dye conjugate 1 was evaluated in three different patient-derived adult glioblastoma cell lines, commercially available U87 glioblastoma, and one paediatric glioblastoma cell line. In all cases, the conjugate 1 showed potent cytotoxic activity with nanomolar potency (EC50 : 267 nM). Interestingly, troxipide alone does not show any cytotoxic and cytostatic activity in the above cell lines. We also observe a synergistic effect of 1 with temozolomide (TMZ), the standard drug used for glioblastoma treatment, even though the cell lines we used in this study were resistant to TMZ treatment. Herein we disclose the synthesis and in vitro activity of drug-dye conjugate 1 for treatment of difficult-to-treat brain cancers such as glioblastoma.